Chronic osteomyelitis in an immunosuppressed patient: Clinical and surgical management (Research, Society and Development, 2025)
Chronic osteomyelitis is a persistent bone infection that presents diagnostic and therapeutic challenges, especially in immunosuppressed patients. The aim of this study is to present a case report based on previously published scientific literature, analyzing the clinical and surgical approach to the management of osteomyelitis in an immunosuppressed patient. The methodology was structured based on the review of clinical cases described in indexed articles, ensuring ethical compliance and scientific relevance. Treatment involved prolonged antibiotic therapy and surgical intervention to remove necrotic tissue, highlighting the importance of a multidisciplinary approach. The study reinforces the need for early diagnosis and personalized therapeutic strategies to improve the prognosis of these patients.